2019
DOI: 10.3390/e21050521
|View full text |Cite
|
Sign up to set email alerts
|

Is Independence Necessary for a Discontinuous Phase Transition within the q-Voter Model?

Abstract: We ask a question about the possibility of a discontinuous phase transition and the related social hysteresis within the q-voter model with anticonformity. Previously, it was claimed that within the q-voter model the social hysteresis can emerge only because of an independent behavior, and for the model with anticonformity only continuous phase transitions are possible. However, this claim was derived from the model, in which the size of the influence group needed for the conformity was the same as the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Binary opinions are probably the most frequently used microscopic dynamical variables in models of opinion dynamics, such as the linear voter 23 , 44 47 and non-linear voter 6 , 13 , 18 , 36 40 , 48 50 models, or the majority-vote model 7 , 8 , 10 , 11 , 20 , 43 , 51 55 . However, it seems that the binary opinion format is not always sufficient and thus the multi-state versions of the voter 23 28 , as well as majority-vote model 21 , 22 , 29 32 was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Binary opinions are probably the most frequently used microscopic dynamical variables in models of opinion dynamics, such as the linear voter 23 , 44 47 and non-linear voter 6 , 13 , 18 , 36 40 , 48 50 models, or the majority-vote model 7 , 8 , 10 , 11 , 20 , 43 , 51 55 . However, it seems that the binary opinion format is not always sufficient and thus the multi-state versions of the voter 23 28 , as well as majority-vote model 21 , 22 , 29 32 was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it seems justified to search for such similarities in other related nonequilibrium models. Taking into account that in the noisy q-voter model on random graphs many results in the MFA and PA can be obtained analytically [13][14][15][16][17][18][19], this model, with a sort of AFM interactions included, could be a good candidate for further studies in the abovementioned direction.…”
Section: Discussionmentioning
confidence: 99%
“…It is often investigated by means of nonequilibrium models formed of agents expressing discrete opinions on a given subject, placed in nodes and interacting via edges of a fixed network with topology reflecting the complexity and, possibly, heterogeneity of social contacts [2,3]. Widely studied examples of such models comprise, e.g., the voter model [4][5][6][7][8], the q-voter model called also nonlinear voter model [9][10][11][12], variants of the noisy q-voter model with different forms of stochasticity [13][14][15][16][17][18][19][20][21][22][23], in particular the q-voter model with independence or anticonformism [13][14][15][16]22], the q-neighbor Ising model [24][25][26][27][28] and the majority-vote model [29][30][31][32][33][34][35]. As a rule, in these models, agents can express only one of two possible opinions and thus are represented by two-state spins and interactions between agents have a form of exchange interactions, either explicitly, as in the q-neighbor Ising model, or effectively, in the remaining models.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, let us also note that, in general, a typical way (Landau approach) to examine the stability of the solutions is to approximate with a suitable polynomial (usually of order 4 or 6) and obtain results for critical points. However, it has been shown that even for relatively simple systems [ 30 ] this analysis might not bring the expected outcomes. Moreover, due to high complexity of the problem (high values of and ) one would need to use high orders of polynomials, making it hard to evaluate in an analytical way.…”
Section: Resultsmentioning
confidence: 99%